Blad-Containing Oligomer Fungicidal Activity on Human Pathogenic Yeasts. From the Outside to the Inside of the Target Cell - Pinheiro, Ana M.; Carreira, Alexandra; Rollo, Filipe; Fernandes, Rui; Ferreira, Ricardo B.; Monteiro, Sara A. (Frontiers in Microbiology, 2016)
Blad polypeptide comprises residues 109 to 281 of Lupinus albus β-conglutin precursor. It occurs naturally as a major subunit of an edible, 210 kDa oligomer which accumulates to high levels, exclusively in the cotyledons of Lupinus seedlings between the 4th and 14th day after the onset of germination. Blad-containing oligomer (BCO) exhibits a potent and broad spectrum fungicide activity towards plant pathogens and is now on sale in the US under the tradename Fracture™. In this work we demonstrate its antifungal activity towards human pathogens and provide some insights on its mode of action. BCO bioactivity was evaluated in eight yeast species and compared to that of amphotericin B. BCO behaved similarly to amphotericin B in what concerns both cellular inhibition and cellular death. As a lectin, BCO binds strongly to chitin. In addition, BCO is known to possess ‘exochitinase’ and ‘endochitosanase’ activities. However, no clear disruption was visualized at the cell wall after exposure to a lethal BCO concentration, except in cell buds. Immunofluorescent and immunogold labeling clearly indicate that BCO enters the cell, and membrane destabilization was also demonstrated. The absence of haemolytic activity, its biological origin, and its extraordinary antifungal activity are the major outcomes of this work, and provide a solid background for a future application as a new antifungal therapeutic drug. Furthermore, its predictable multisite mode of action suggests a low risk of inducing resistance mechanisms, which are now a major problem with other currently available antifungal drugs.